Research on Android app Vs Apple app Market: Who is leading? (International Journal of Engineering and Computer Science, 2014)
Now days there is boom of smart phones, there are more than a billion smartphone users in the world [1]. As of 2013, two-third of Americans own smartphones [2].The key feature of these smart phones are their application support and there operating system on which these application runs. The most common mobile operating systems are Android, iOS, Blackberry and WindowsPhone.This paper provides detail analysis of market share of smart phones having different mobile operating systems.